Fusobacterium nucleatum Acts as a Pro-carcinogenic Bacterium in Colorectal Cancer: From Association to Causality - Wang, Shuang; Liu, Yang; Li, Jun; Zhao, Lei; Yan, Wei; Lin, Baiqiang; Guo, Xiao; Wei, Yunwei (Frontiers in Cell and Developmental Biology, 2021)
Colorectal cancer (CRC) is a common cancer worldwide with complex etiology. Fusobacterium nucleatum (F. nucleatum), an oral symbiotic bacterium, has been linked with CRC in the past decade. A series of gut microbiota studies show that CRC patients carry a high abundance of F. nucleatum in the tumor tissue and fecal, and etiological studies have clarified the role of F. nucleatum as a pro-carcinogenic bacterium in various stages of CRC. In this review, we summarize the biological characteristics of F. nucleatum and the epidemiological associations between F. nucleatum and CRC, and then highlight the mechanisms by which F. nucleatum participates in CRC progression, metastasis, and chemoresistance by affecting cancer cells or regulating the tumor microenvironment (TME). We also discuss the research gap in this field and give our perspective for future studies. These findings will pave the way for manipulating gut F. nucleatum to deal with CRC in the future.